Solving the Quadratic Equation: (x + 1)(x + 3) = 0
This equation represents a simple quadratic equation in factored form. To solve for the values of x that satisfy the equation, we can utilize the Zero Product Property.
The Zero Product Property
The Zero Product Property states that if the product of two or more factors is zero, then at least one of the factors must be zero.
In our case, we have two factors: (x + 1) and (x + 3). To satisfy the equation, at least one of these factors must equal zero.
Solving for x
Let's set each factor equal to zero and solve for x:

Factor 1: (x + 1) = 0
 Subtract 1 from both sides: x = 1

Factor 2: (x + 3) = 0
 Subtract 3 from both sides: x = 3
The Solutions
Therefore, the solutions to the equation (x + 1)(x + 3) = 0 are x = 1 and x = 3.
These solutions represent the roots of the quadratic equation, which are the points where the graph of the equation intersects the xaxis.